Effect of Compression Ratio on the Performance of Different Strategies for the Gas Turbine - Ibrahim, T. K.; M. M., Rahman (Universiti Malaysia Pahang, 2014)
Finding clean and safe energy is the greatest challenge to meeting the requirements of a green environment. These requirements given way the long time governing authority of steam turbine (ST) in the world power generation, and gas turbine (GT) will replace it. It is therefore necessary to predict the characteristics of the GT and optimize its operating strategy by developing a simulation system. Several configurations of GT plants are proposed by thermal analysis. The integrated model and simulation code for exploiting the performance of GT plants have been developed using MATLAB code. The performance codes for heavy-duty GT power plants were validated with the Bassily model and the results have been satisfactory. Results of performance enhancing strategies show that higher power output occurs in the intercooler-reheat GT (IHGT) strategy (286 MW). At a compression ratio of 12.4 in the intercooler-regenerative-reheat GT (IRHGT) strategy, the highest (best) thermal efficiency obtained was 50.7%. In the IHGT, the lowest thermal efficiency obtained was 22% to 39.3% in the presence of a compression ratio between 3 and 30. The lowest fuel consumption (0.14 kg/kWh) occurred in the IRHGT strategy. Compression ratios are thus strongly influenced by the overall performance of the GT.